Dynamic analysis of co-curing double-layer damping films embedded composite beam with fixed-support boundary. (August 2022) - Yang, Gongxian; Liang, Sen; Zheng, Changsheng; Wang, Guanghe
Co-curing double-layer damping films embedded composite structure has many advantages over a tradition composite, such as large damping, high specific strength etc. In order to study the dynamic performance of this composite clamped beams, a theoretical model of the free vibration of the beam was established by the combination of first-order shear deformation theory with the Hamilton principle and variational principle. The Galerkin method was presented to find the free vibration theoretical solution under the fixed-support boundary conditions. The theoretical solution was compared with the experimental results through the established experimental platform. According to the comparison results, the validity of the theoretical model was proved. Finally, the effects of the damping layer distribution and the geometric parameters on the dynamic performance were further explored. It provides a theoretical basis for the optimal configuration of double-layer damping films embedded composite clamped beams structure.